An Analysis of Biology Students’ Creative Thinking ability in Ethnobotany Course - Handayani, Isnaini Siwi; Zaini, Muhammad; Dharmono, Dharmono; Wulandari, Eka (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2022)
This study aimed to describe the creative thinking ability of biology students in the ethnobotany course. The type of research used was descriptive research using a quantitative approach. The research subjects were 28 students taking ethnobotany courses in the Biology Study Program at IAIN Palangka Raya. The data were collected using the question instrument. Fluency, flexibility, originality, elaboration, and evaluation indicators of creative thinking ability. The results show that students' creative thinking abilities were divided into high, medium, and low. The creative thinking ability of biology students was dominantly in the low category. The students' creative thinking ability in the high category was evaluation. Furthermore, the students' creative thinking ability in the medium category was fluency, and the low categories were flexibility, originality, and elaboration. These results urged that teaching materials be developed to improve students' creative thinking ability.ABSTRAK: Penelitian ini bertujuan untuk mendeskripsikan kemampuan berpikir kreatif mahasiswa tadris biologi pada mata kuliah etnobotani. Jenis penelitian yang digunakan adalah penelitian deskriptif dengan menggunakan pendekatan kuantitatif. Subjek penelitian adalah 28 mahasiswa yang sedang menempuh mata kuliah etnobotani pada program studi tadris biologi di IAIN Palangka Raya. Pengambilan data menggunakan instrumen soal. Indikator kemampuan berpikir kreatif yang digunakan yaitu fluency, flexibility, originality, elaboration, dan evaluation. Hasil menunjukkan bahwa kemampuan berpikir kreatif mahasiswa dibagi menjadi tiga kategori yaitu tinggi, sedang dan rendah. Kemampuan berpikir kreatif mahasiswa tadris biologi pada mata kuliah etnobotani yang dominan adalah dalam kategori rendah. Kemampuan berpikir kreatif mahasiswa yang kategori tinggi yaitu evaluasi, kategori sedang yaitu kelancaran dan kategori rendah yaitu fleksibilitas, orisinalitas, dan elaborasi. Hasil ini mengindikasikan bahwa perlu dikembangkan bahan ajar untuk meningkatkan kemampuan berpikir kreatif mahasiswa.